2016
DOI: 10.5430/ijfr.v7n2p18
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effectiveness of Audit Committees in the UK and Turkish Banks

Abstract: The audit committee effectiveness (ACE) has been researched for several times by academics in accounting and finance literature in terms of relationships with earnings management, corporate governance mechanism, power types and, audit fee etc. This study aims to measure of the emphasize of effective audit committees (ACs) on bank performance via using some of the main bank performance indicators which are return on asset (ROA), return on equity (ROE) and net interest margin (NIM) in the Turkish and the UK bank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Also, the number of independent members of the audit committee has a negative impact on bank financial performance. The more member of the independent audit committee, the lower the percentage of ROA, ROE, and NIM (Gunes & Atilgan, 2016;Yasin & Nelson, 2012). Even the audit committees that often doing a meeting do not prevent earning management practices (Zgarni et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the number of independent members of the audit committee has a negative impact on bank financial performance. The more member of the independent audit committee, the lower the percentage of ROA, ROE, and NIM (Gunes & Atilgan, 2016;Yasin & Nelson, 2012). Even the audit committees that often doing a meeting do not prevent earning management practices (Zgarni et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Inversely, some previous studies found that audit committee characteristics not improving the quality of financial reporting (Wiralestari & Tanzil, 2015). The number of independent members of the audit committee has a negative impact on bank financial performances as a means of ROA, ROE, and NIM (Gunes & Atilgan, 2016). An audit committee that was often doing a meeting does not prevent earning management practice in the company (Zgarni, Fadhila, & El Gaied, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Material facts, if not included, will mislead investors and other stakeholders. Therefore, it is essential to understand that the interpretation and meaningful analysis of financial statements that these basic concepts, hypotheses, principles and conventions used in the preparation must be constantly considered (Gunes & Atilgan, 2016).…”
Section: The Problemmentioning
confidence: 99%
“…Similarly, Aanu et al (2014), Wakaba (2014), Nuhu et al (2017), Zabojnikova (2016) and Amer (2014) have revealed a positive relationship between the AC financial expertise and firm performance. However, Gunes and Atilgan (2016) in Turkish banks and Glover-Akpey and Azembila (2016) in Ghanaian firms have established a negative relationship between AC financial expertise and bank performance.…”
Section: Professional Finance Educationmentioning
confidence: 99%